Modelling of microstructural changes in heterogenous joints. - Karaaslan, Ahmet (CARL HANSER VERLAG, 2006)
The knowledge of the weld metal properties is a fundamental aspect for the evaluation of weldability. In many cases the chemical composition combined with thermodynamical calculations are sufficient to evaluate the quality of the joint and the various microstructures which might be expected in various welds and in the respective transformation zones. The present contribution highlights the microstructure prediction based on thermodynamical calculations of the constitutional variations for various dilutions of the materials to be welded.
Keywords: Materials Science